Analysis and estimation of the application of selected sweeteners used in food by consumers. Part 1 - Rusek, Anna; Biazik, Ewa; Lesiów, Tomasz (Engineering Sciences And Technologies, 2016)
Sweeteners such as disaccharides, mannitol, lactitol, sorbitol, xylitol and many others are either purchased by consumers separately or they are added to highly processed food products. These substances can be used in pastry, cakes, beverages and dairy products. The aim of the study was to analyse the application of selected types of sweeteners by Polish consumers. The research was conducted in 2016 and the respondents were interviewed using questionnaires. Almost half (45%) of the respondents drew attention to sweeteners added to food products, especially beverages, sweets, yoghurts, juices, jams, marmalades and confections. Among the different types of food categories with added sweeteners, consumers enumerated primarily pastry products, processed fruit products, dairy and cereal products. The respondents declared that they used sweeteners because of a willingness to reduce the amount of sugar and this was connected with their health and well-being (35%). Moreover, consumers gave the reason for the use of sweeteners as being the less intense sweetness of these substances (13% of respondents) and the desire to lose weight (11% of respondents)
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2016, Nr 3 (22), s. 101-115
Keywords: sweeteners; consumer preferences; substancje słodzące; preferencje konsumentów